Aktifitas Antimikroba Ekstrak Fraksi n-Heksan Daun Sungkai (Peronema canescens. JACK) terhadap Beberapa Bakteri dengan Metode KLT-Bioautografi (Journal of Tropical Pharmacy and Chemistry, 2013)
Infectious diseases are still a serious problem in Indonesia, as well as the more widespread microbial resistance to antibiotics available. Traditional medicinal plants known potential to be developed as a source of infectious disease treatment is Sungkai Plant (Peronema canescens. Jack). This study aims to determine the antimicrobial activity of leaf  extracts of n-hexane Sungkai with KLT-bioautografi method against some microbial testing. Microbial testing is used as much as 3 types of gram-positive bacteria that is Basillus subtillis, Streptococcus mutans and Staphylococcus  aureus.  The extraction  method used to  get  the n-hexane fraction obtained from liquid-solid partition using n-hexane. Preliminary research conducted by the screening test n-hexane extract of the solid dilution method with DMSO as a negative control. Preliminary results obtained n-hexane extract gave growth inhibition against all the test bacteria at levels of 1 mg / ml. while the antibacterial activity of the test results-bioautografi TLC method showed some active spots with a diameter of clear zone and a different price Rf. Active spot detection using stain apparition UV 254 nm, 366 nm and 10% H2SO4 spray reagent. Active Spot-bioautografi KLT test results obtained by the four active spots on three types of bacteria that test B. subtillis, St. mutans and S. aureus with Rf value detection results reagent H2SO4 10%, respectively each is Rf 0.75 cm with brown spots, Rf 0, 68 cm purple, brown Rf 0.29 cm and Rf 0.21 cm brown.